2008
DOI: 10.17221/1993-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

In vitro production of embryos from high performance cows and the development of frozen-thawed embryos after transfer: a field study

Abstract: AbstrAct:In this field study, embryos were derived from genetically highly valuable cows excluded from breeding due to reproductive disorders. Cows, 5 to 10 years old, of Czech Siemmental, Holstein Dairy and Beef Cattle breeds were used as oocyte donors. Oocytes were obtained either in the growth phase of the first follicular wave from cows with synchronized oestrus or in any other phases of follicular development from cows without oestrus synchronization. The embryos were prepared by a standard protocol descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
2
2
Order By: Relevance
“…Overall, the development of embryos produced in vitro was low across all breeds compared to their in vivo counterparts. This study is comparable with the findings of Machatkova et al, (2008) and Lonergan and Fair (2014) who indicated that the development of embryos produced in vitro from oocytes of selected donors and survival of these embryos after cryopreservation was low compared with embryos produced in vivo from superovulated donors.…”
Section: Resultssupporting
confidence: 90%
“…Overall, the development of embryos produced in vitro was low across all breeds compared to their in vivo counterparts. This study is comparable with the findings of Machatkova et al, (2008) and Lonergan and Fair (2014) who indicated that the development of embryos produced in vitro from oocytes of selected donors and survival of these embryos after cryopreservation was low compared with embryos produced in vivo from superovulated donors.…”
Section: Resultssupporting
confidence: 90%
“…We only found a lower rate reported previously in Czech beef breeds (Machatkova et al, 2008) and in zebu Nelore cows (Dode et al, 2001). It is noteworthy that the low number of replicates could influence the results obtained.…”
contrasting
confidence: 83%
“…Oocyte recovery rates observed in our study are shown in Table 1 These results were lower than previous reports by several authors in other cattle breeds: 4.60 in Podolian and 5.83 in Maremmana (Pauciullo et al, 2012); 5.33 in Czech Simmental and 6.50 in dairy Holstein (Machatkova et al, 2008); 9.5 in Belgium Holstein and 11.1 in Belgium Blue (Van Soom et al, 1993). We only found a lower rate reported previously in Czech beef breeds (Machatkova et al, 2008) and in zebu Nelore cows (Dode et al, 2001).…”
contrasting
confidence: 74%
“…Under optimal conditions, pregnancy rates obtained after transfer of frozen-thawed in vivo derived embryos is typically 60-70% in cattle 6,7 , 65-75% in sheep 8,9,10,11 , and 60-70% in goats 12,13,14,15 . Similarly, pregnancy rates obtained after transfer of frozen-thawed in vitro produced embryos is typically 40-50% in cattle 6,16 , 25-35% in sheep 17 , and 30-40% in goats 18 . Table 1.…”
Section: Representative Resultsmentioning
confidence: 99%